FAKTOR-FAKTOR YANG MEMPENGARUHI PENINGKATAN MARKET SHARE BANK UMUM SYARIAH (BUS) DI INDONESIA - Ismi Mauli Desil; Amri Amri (JURNAL ILMIAH MAHASISWA EKONOMI ISLAM, 2020)
The purpose of this research is to analyze the influence of Non Performing Financing (NPF), Operating Expenses to Operating Income (BOPO), and Capital Adequacy Ratio (CAR) on the market share of sharia commercial banks in Indonesia. The target population of the object of this research are 13 sharia commercial banks registered at Financial Service Authority and publish annual reports from period 2014 to 2017. The dependent variable used in this research is the market share of sharia commercial banks, while the independent variables are NPF, BOPO, and CAR. Based on analysis of multiple linear regression panel data using the random effect model method, indicate that simultaneously NPF, BOPO, and CAR have a significant influence on the market share of sharia commercial banks in Indonesia. Partially, NPF has a positive and significant influence, while BOPO and CAR have negative and significant influence on the market share of sharia commercial banks.  The variable of BOPO has the most dominant influence on the variable market share of sharia commercial banks. Based on the result of this research, it is expected that sharia commercial banks can suppress NPF, reduce BOPO, and improve CAR accompanied by good management to increase market share of sharia commercial banks in Indonesia.